Predictors of serious adverse events and non‐response in cirrhotic patients with primary biliary cholangitis treated with obeticholic acid. (23rd August 2022) - De Vincentis, Antonio; D'Amato, Daphne; Cristoferi, Laura; Gerussi, Alessio; Malinverno, Federica; Lleo, Ana; Colapietro, Francesca; Marra, Fabio; Galli, Andrea; Fiorini, Cecilia; Coco, Barbara; Brunetto, Maurizia; et al.
Abstract: Background & Aims: Obeticholic acid (OCA) has recently been restricted in patients with primary biliary cholangitis (PBC) with "advanced cirrhosis" because of its narrow therapeutic index. We aimed to better define the predicting factors of hepatic serious adverse events (SAEs) and non‐response in cirrhotic patients undergoing OCA therapy. Methods: Safety and efficacy of treatment were evaluated in a cohort of consecutive PBC cirrhotic patients started with OCA. OCA response was evaluated according to the Poise criteria. Risk factors for hepatic SAEs and non‐response were reported as risk ratios (RR) with 95% confidence intervals (CIs). Results: One hundred PBC cirrhotics were included, 97 Child‐Pugh class A and 3 class B. Thirty‐one had oesophageal varices and 5 had a history of ascites. Thirty‐three per cent and 32% of patients achieved a biochemical response at 6 and 12 months respectively. Male sex (adjusted‐RR 1.75, 95%CI 1.42–2.12), INR (1.37, 1.00–1.87), Child‐Pugh score (1.79, 1.28–2.50), MELD (1.17, 1.04–1.30) and bilirubin (1.83, 1.11–3.01) were independently associated with non‐response to OCA. Twenty‐two patients discontinued OCA within 12 months: 10 for pruritus, 9 for hepatic SAEs (5 for jaundice and/or ascitic decompensation; 4 for upper digestive bleeding). INR (adjusted‐RR 1.91, 95%CI 1.10–3.36), lower albumin levels (0.18, 0.06–0.51), Child‐Pugh score (2.43, 1.50–4.04), history of ascites (3.5, 1.85–6.5) and bilirubin (1.30, 1.05–1.56), were associated with hepatic SAEs. A total bilirubin≥1.4 mg/dl at baseline was the most accurate biochemical predictor of hepatic SAEs under OCA. Conclusions: An accurate baseline assessment is crucial to select cirrhotic patients who can benefit from OCA. Although OCA is effective in one third of cirrhotics, bilirubin level ≥1.4 mg/dl should discourage from its use.